First record of the fangtooth snake-eel, Aplatophis chauliodus Böhlke 1956 (Anguilliformes: Ophichthidae), from the Caribbean coast of Costa Rica, Central America - Vidaurre Quesada, Naidely (2025)
The presence of Aplatophis chauliodus is reported for the first time in the southern Caribbean coast of Costa Rica. The record is based on a specimen of 590 mm in total length, captured at a depth of 10 m. This report extends the known distribution range of the species in the Caribbean Sea by more than 400 km to the west. Morphometric and meristic data are provided and discussed for comparison purposes.